1997
DOI: 10.1021/ja970754m
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Highly Luminescent CdSe/CdS Core/Shell Nanocrystals with Photostability and Electronic Accessibility

Abstract: The synthesis of epitaxially grown, wurtzite CdSe/CdS core/shell nanocrystals is reported. Shells of up to three monolayers in thickness were grown on cores ranging in diameter from 23 to 39 Å. Shell growth was controllable to within a tenth of a monolayer and was consistently accompanied by a red shift of the absorption spectrum, an increase of the room temperature photoluminescence quantum yield (up to at least 50%), and an increase in the photostability. Shell growth was shown to be uniform and epitaxial by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

94
2,231
3
16

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,391 publications
(2,344 citation statements)
references
References 42 publications
(80 reference statements)
94
2,231
3
16
Order By: Relevance
“…The varying results for QY changes after peptide coating for samples [1][2][3][4][5] show that the shell composition/structure is a major factor in the QY of peptide-coated NCs. In all cases besides CdSe/ZnS, QY and emission changes similar to those in Table 1 were acquired with cores of different sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The varying results for QY changes after peptide coating for samples [1][2][3][4][5] show that the shell composition/structure is a major factor in the QY of peptide-coated NCs. In all cases besides CdSe/ZnS, QY and emission changes similar to those in Table 1 were acquired with cores of different sizes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although NR 6 has the longest CdS rod length, we achieved almost the same amount ($8 nm) of blue-shied ASE from NR 6 when compared to NR 5 . It is also shown that both NR 5 and NR 6 have the same radiative lifetime, which conrms that photoluminescence lifetimes are a good indicator of connement. Finally, optical gain thresholds down to 3 mJ cm À2 are achieved 5 Normalized decomposed ASE and spontaneous emission spectra of (a) NR 4 , (b) NR 5 and (c) NR 6 samples under intense twophoton optical pumping.…”
mentioning
confidence: 81%
“…The solution of CdSe seeds in TOP can be added to the reaction mixture either together with TOPS or 30-60s later, i.e., during the induction period. CdS easily nucleates at the surface of CdSe seeds [11,17]. We found that the structure of the CdSe seeds determined the morphology of CdSe/CdS nano-heterostructures.…”
mentioning
confidence: 83%
“…In this work we compared w-CdSe and zb-CdSe nanocrystals for seeded growth of CdSe/CdS nano-hererostructures with different morphologies. Combining CdSe and CdS in a single nanostructure creates a material with heterogeneous carrier confinement or "mixed dimentionality" where holes are confined to CdSe while electrons can move freely between CdSe and CdS phases, spreading over the entire nanostructure [11,17]. Previously we synthesized structures consisting of a spherical CdSe nanocrystal connected to a CdS nanorod [17].…”
mentioning
confidence: 99%